Political Corruption : In and Beyond the Nation State. (Taylor & Francis, 2003)
This important new book examines political corruption from three perspectives. First it asks, what is political corruption? This seemingly simple question transpires to be anything but simple. Is political corruption so different from politics itself? How does it relate to presidential power, pressure group politics, party funding and economic liberalisation? Secondly, in two national case studies, of China and the United Kingdom, it shows political corruption taking different forms in different countries: in one of these countries political corruption remains persuasive; in the other it has largely disappeared. Thirdly, it looks at international and transnational corruption, asking how well equipped the nation state system is to deal with crimes that cross state boundaries. For much transnational criminality, from the drug trade to people trafficking, from nuclear sales to money laundering, thrives with the connivance of corrupt politicians. This book, combining scholarship with readability, shows that political corruption must itself be analysed politically.; Spectacularly corrupt politicians - the exception rather than the rule - are usually symptoms, not causes, and much political corruption is simply normal politics taken to excess. But in a world in which anti-corruption strategies themselves are often thinly disguised examples of political corruption, the ways in which political systems address their own corruption are as varied and fascinating in character as crucial to comprehend. A valuable read for anyone studying social science disciplines such as politics, international relations, sociology, anthropology, criminology and public policy. As well as the global community of anti-corruption activists, professional politicians, police, business people and lawyers.